Answering the Big Clinical Questions in Brain Metastasis Management - Kirkpatrick, John P. (Frontiers in Oncology, 2022)
Management of brain metastases is challenging, both because of the historically guarded prognosis and evolving, more efficacious treatment paradigms for metastatic cancer. This perspective addresses several of the important difficult questions that practitioners treating patients with brain tumors face in the clinic. Successfully answering these questions requires knowledge of the clinical evidence, thoughtful discussion of the patient’s goals of care and collaboration in a multi-disciplinary setting.